EFEKTIVITAS PENGGUNAAN GAME EDUKASI BERBASIS WORDWALL DALAM MENINGKATKAN HASIL BELAJAR MATEMATIS SISWA - Anggriany, Nabila; Rakhmawati, Fibri (Universitas Bhinneka PGRI, 2024)
This research aims to determine the effectiveness and practicality of using wordwall-based educational games. This research method is RD using a 4D model. Two validators assessed the validity of wordwall-based educational games: material validator and media validator, then carried out practicality and effectiveness tests. The research results show that with a maximum scale of 4.00, the material validation value shows 3.10, and the media validation value shows 3.61. This shows that wordwall-based educational games can be used in a practical way. The average percentage of practicality of wordwall-based educational games is 80.93%, indicating that it is very practical. Apart from that, wordwall-based educational games are considered quite effective with an N-Gain value of 0.3489 for the effectiveness test. Therefore, the wordwall-based educational game developed can be said to be effective in improving students' mathematical learning outcomes.